Identification for Development : Kenya - World Bank Group (World Bank, Washington, DC, 2016)
Identification schemes are key enablers for the effective delivery of services and more broadly for the quality of engagement between a country’s government and its citizens. Legal identity is now recognized as an essential element of development; target 16.9 of the Sustainable Development Goals (SDGs) refers to the provision of universal legal identity, including through birth registration, by 2030. Legal identity is central to the rights set out, for example, in the Declaration of Human Rights and the Convention on the Rights of the Child. In addition, effective identification is important for at least ten of the other SDGs. This assessment of Kenya’s ID system was undertaken under the umbrella of the World Bank Identification for Development (ID4D) initiative. Its general objective is to map out the system, identify its ID assets and suggest areas where they can be strengthened. More specifically, the Bank is engaged in supporting a number of transfer and similar programs that place particular demands on identification systems through the National Safety Net Program for Results and is also financing the Kenya Transparency and Communications Infrastructure (KTCIP) project to scale up digital inclusion and e-Government. This project includes the digitization of registration data. In order to address these issues a World Bank mission visited Kenya May 18–28. Its broad objective was to better understand the nature and capabilities of Kenya’s ID system, its role in development and how best to work with the country to strengthen this. The mission also sought to assess the ID system from the perspectives of the identification needs of the operational engagements and their current and potential role in strengthening the system of civil registration and identification. The mission met with stakeholders from both the supply and demand sides of the ID system and thanks the Government of Kenya for facilitating open and comprehensive discussions.